Heterogeneity of the CYP2D6 gene among Malays in Malaysia - Teh, L.K.; Ismail, R.; Yusoff, Rozita; Hussein, A.; Isa, M.N.; Rahman, A.R.A. (Wiley, 2001)
Background: Although Malays shared an origin with Chinese, their evolution saw substantial divergences. Phenotyping studies suggested that they differed in CYP2D6 polymorphism, with higher PM prevalence but lesser right-shift for debrisoquine MRs. Objective: To study the genotype distribution of CYP2D6 among the Malays in Malaysia. Method: We obtained DNA from 107 Malays and used PCR to determine common CYP2D6 alleles. Result:CYP2D6*1 occurred at a frequency of 36·0, duplicated gene, 0·93, CYP2D6*4, 2·8, CYP2D6*5, 5·1, CYP2D6*9, 3·3, CYP2D6*10, 49·5 and CYP2D6*17, 0·5. The findings of CYP2D6*17 and CYP2D6*9 were novel for Asia. The frequency for CYP2D6*10 was lower than in other Asian races. The most frequent genotypes were CYP2D6*1/*10 at 39·3. Two subjects had genotypes that predicted PM phenotype, 35 showed genotypes that predicted intermediate metabolizers and one subject had a genotype that predicted ultra-rapid metabolism. Conclusion: The genetic polymorphism of CYP2D6 in Malays is different from Chinese and Far Eastern races. They may be intermediate between East Asians and Caucasians in CYP2D6 activity. Further study in relation to the evolution of races and disease prevalence may help to identify the contributions of the polymorphism in alleged susceptibility to diseases apart from delineating its contributions to ethnic differences in the pharmacology of CYP2D6 drugs.